The Law Enforcement Of The Police Station Of Ternate In Overcoming The Liquor Distribution In Ternate City Communities - Gunawan Hi Abas; Tri Arso (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
The concrete legal problem addressed in Ternate is that the center of the supply of liquor (miras) is very high from various centers of Halmahera which originate from different places and are exported by sea so that it makes it a bit difficult for the police to detect it. Liquor, which is widely consumed across the community, is even traded in a free place, ironically again among the younger generation, students, who can get it in a freely accessible place. Alcohol consumption contributes to negative behaviors and attitudes like speeding on the highway, which can disturb traffic, disturb the peace, and create noise and chaos. This is due to excessive drinking, which leads to diminished willpower. Several calls for the local government of Ternate to take greater care in controlling liquor availability. Also, there are multiple signals in regards to legislation, regional regulations, the law enforcement officials' implementation, and the community's legal culture. Thus, the role of law enforcers is placed within the context of realizing the objectives of the law with security and order for individual’s realization of a peaceful and prosperous society. The regional government together with the DPRD of Ternate to be asked to immediately amend the Regional Regulation of Ternate Number 5 of 2004 concerning alcohol, which is considered not able to trigger a deterrent effect because the penalties regulated in the current Ternate municipal, regional regulations stipulate the maximum penalty, should be able to substitute with minimal penalties to have a deterrent effect on liquor sellers and consumers.